The Level of Awareness on Data Privacy Act Among the Selected Employees in Metro Manila - Jumaquio, Joffer (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to assess the level of awareness of selected government and private employees in Metro Manila regarding the Data Privacy Act of 2012 (Republic Act No. 10173). Anchored on Organizational Compliance Theory (Weaver, Treviño, & Cochran, 1999) and the legal framework of the Data Privacy Act, the study examined how awareness, organizational practices, and compliance mechanisms influence data privacy implementation. A quantitative research design was employed using a structured and validated survey questionnaire administered to 110 respondents selected through stratified random sampling from one government and one private institution. Data were analyzed using frequency, percentage, and weighted mean. Findings revealed that respondents, despite having high educational attainment and extensive years of service, demonstrated only a slight level of awareness of the Data Privacy Act, with a grand mean of 2.44. While they were highly aware of the importance of protecting personal and sensitive information, they showed low awareness regarding mandatory training and penalties for non-compliance. The study also identified significant issues and challenges, particularly inadequate training, low awareness of key provisions, limited resources, and insufficient technological capability, which contributed to compliance difficulties (AWM = 3.12). In response, the proposed solutions—rated as highly recommended (AWM = 3.39)—emphasized regular training programs, improved cybersecurity systems, integration of data privacy education into organizational processes, and capacity-building initiatives. The study concluded that enhancing employee awareness through continuous training and strengthening institutional capabilities are critical for improving compliance with data privacy regulations. The findings align with SDG 16 (Peace, Justice, and Strong Institutions) by promoting accountability, data protection, and institutional integrity, and SDG 4 (Quality Education) through the emphasis on continuous learning and capacity-building. In terms of sustainability impact, the study contributes to strengthening organizational governance, improving data protection practices, and fostering a culture of accountability and security within institutions, thereby supporting long-term institutional resilience and public trust.
Keywords: Awareness; Compliance; Data Privacy Act of 2012; Data Protection; Government Employees; Metro Manila; Organizational Compliance; Private Employees